1996
DOI: 10.1103/physrevb.54.5438
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-drag effects on thermoelectric power

Abstract: We carry out a calculation of the phonon-drag contribution Sg to the thermoelectric power of bulk semiconductors and quantum well structures for the first time using the balance equation transport theory extended to the weakly nonuniform systems. Introducing wavevector and phononmode dependent relaxation times due to phonon-phonon interactions, the formula obtained can be used not only at low temperatures where the phonon mean free path is determined by boundary scattering, but also at high temperatures. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Consequently, , should correspond to an S d value of 0. The observed nonzero value of S is reflective of two facts: 1) S g , the phonon-drag component of S, has not been taken into account, which could be significant at this temperature, [46] and 2) S m , the thermoelectric power of Pt/Ti electrodes used to establish the thermocouple with Bi nanowires, has not been considered. The Pt/Ti electrodes are not expected to contribute to the EFE due to their extremely small screening lengths, [44] but they might cause a uniform shift -S m in S at all V g .…”
Section: R(t)/r (300k)mentioning
confidence: 82%
“…Consequently, , should correspond to an S d value of 0. The observed nonzero value of S is reflective of two facts: 1) S g , the phonon-drag component of S, has not been taken into account, which could be significant at this temperature, [46] and 2) S m , the thermoelectric power of Pt/Ti electrodes used to establish the thermocouple with Bi nanowires, has not been considered. The Pt/Ti electrodes are not expected to contribute to the EFE due to their extremely small screening lengths, [44] but they might cause a uniform shift -S m in S at all V g .…”
Section: R(t)/r (300k)mentioning
confidence: 82%
“…They found that smaller Te dots exhibit higher S than larger Te dots, as revealed in Figure h. This is because smaller Te dots (≈2 nm) can prevent inefficient phonon scattering in the composites, which would otherwise lower S according to the phonon‐drag theory . With a tuned doping level for enhancing σ, a peak S 2 σ of ≈100 µW m −1 K −2 has been achieved at room temperature …”
Section: Strategies To Optimize Organic/inorganic Hybridsmentioning
confidence: 94%
“…Since we are interested in deriving general properties, we do not solve the problem using a full hydrodynamical approach where a complete analysis of the momentum transfer between electrons, phonons, and magnons is taken into account. This kind of approach has been used for phonons with moderate success [28], but it is out of the scope of the present work. Instead, we follow a more intuitive approach inspired by the analysis of the magnon drag Peltier effect carried out for a ferromagnetic (FM) chain [29] and spectacularly confirmed for real cases [30].…”
Section: Magnon Drag Contributionmentioning
confidence: 99%